Language in schizophrenia Part 2: What can psycholinguistics bring to the study of schizophrenia…and vice versa? - Kuperberg, Gina R. (2010)
This is the second of two articles that discuss higher-order language and semantic processing in schizophrenia. The companion article (Part 1) gives an introduction to language dysfunction in schizophrenia patients. This article reviews a selection of psycholinguistic studies which suggest that sentence-level abnormalities in schizophrenia may stem from a relative overdependence on semantic associative relationships at the expense of building higher-order meaning. Language disturbances in schizophrenia may be best conceptualized as arising from an imbalance of activity across two streams of processing, one drawing upon semantic relationships within semantic memory and the other involving the use of combinatorial mechanisms to build propositional meaning. I will also discuss some of the ways in which the study of schizophrenia may offer new insights into the cognitive and neural architecture of the normal language system.